Fenotipagem eritrocitária em doadores de sangue no HEMOPI - PI (Teresina - Picos) e no hemocentro regional do Crato - CE - Silva, José Manuel da (2016)
Due to better life expectancy and the aging of population, consequently the improvement of technical advances and diagnostics in medicine, combined with new therapeutic modalities for different diseases, it is growing worldwide the transfusion of packed red blood cells, platelets and fresh frozen plasma. So, the erythrocyte phenotyping as in receptors as in blood donors aims to reduce the number of transfusion reactions, preventing the appearance of antibodies in a later way, mainly in those receptors candidates to poly-transfusion. Besides this the erythrocyte phenotyping is essential for confirmation of formed alloantibodies as well as facilitating the identification of antibodies that can be formed in the future. This study aimed to analyze the frequencies of the main antibodies of blood groups belonging to the systems ABO, Rh, Duffy, Kidd, MNS, and K antigen of Kell system and to study the association between these groups and the distribution concerning the origin and the racial group self-referred. Being these, the main systems involved in hemolytic disease worldwide. 532 samples of blood donors of hemocenter of Ceará State, regional of Crato and hemocenter of Piaui State (Teresina and Picos). The methods used were the techniques of blood typing in hemolysis tube for phenotyping ABO/Rh (Fresenius Kabi). To identify other systems, it was used gel centrifugation with their respective antisera. (Biorad). It was determined the absolute and relative frequencies of categorical variables analyzed. The association between the phenotypes of blood group and region of origin and the self-referred race of donors was evaluated chi-square test. It was adopted as significant P< 0.05. In the current study it was observed that of 532 phenotyped donors , the distribution for males was ( 68.80% ) and females ( 31.20%). As for the frequency of blood systems, the most common groups were: O (53.38%), Jk ( a + b +) (52.26%), Fy (a + b ) ( 35.71%), M + Na s-s + + (21.05%), DCcee (35.54%) and the antigen K negative with ( 96.62% ). As for the phenotypes less frequent it was found the groups : AB (2,26% ) , Jk (0,19% ), Fy ( 8,65% ), M - N + S –s- ( 0,19% ) , M + N - S-s- ( 0,19% ), M+ N +S - s - ( 0,56% ), dCee ( 0,19% ), DCCEe ( 0,38% ) and DccEE ( 3,01% ). As for the region of origin shows there was no association between all phenotypes analyzed and the region of origin between donors. Also, it was not found association between the categories of self-reported race and all phenotypes analyzed. The study provided to know the erythrocyte profile of our donors with respect to the blood groups studied which constitute the main erythrocyte antigens of major clinical importance, contributing to improve the safety, quality and improvement in the practice of transfusion medicine in the states of Ceará and Piauí. From our data on, the meeting of negative units for the main erythrocytes antigens will allow the gathering of blood with rare phenotype in our population. The use of phenotyped red blood cells, along with the proof of compatibility becomes a fundamental tool to foster strategy for stock of blood, reflecting in a fast meeting of an ideal blood for each receptor.